Respostas
respondido por:
3
a = - 9 b= 6 c = -1
(-b (+ ou -) √b² - 4 . a . c) / 2.a
( -6 (+ ou -) √6² - 4 . -9 . (-1)) / 2 . -9
(-6 (+ ou -) √36 - 36) / -18
(-6 (+ ou -) √0 ) / -18
X1 = -6/-18 X2= -6/-18
RESPOSTA ⇒ X = 0,33
(-b (+ ou -) √b² - 4 . a . c) / 2.a
( -6 (+ ou -) √6² - 4 . -9 . (-1)) / 2 . -9
(-6 (+ ou -) √36 - 36) / -18
(-6 (+ ou -) √0 ) / -18
X1 = -6/-18 X2= -6/-18
RESPOSTA ⇒ X = 0,33
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás